Artificial sweeteners – a review - Chattopadhyay, Sanchari (Springer India, 2011)
Now a days sugar free food are very much popular because of their less calorie content. So food industry uses various artificial sweeteners which are low in calorie content instead of high calorie sugar. U.S. Food and Drug Administration has approved aspartame, acesulfame-k, neotame, cyclamate and alitame for use as per acceptable daily intake (ADI) value. But till date, breakdown products of these sweeteners have controversial health and metabolic effects. On the other hand, rare sugars are monosaccharides and have no known health effects because it does not metabolize in our body, but shows same sweet taste and bulk property as sugar. Rare sugars have no such ADI value and are mainly produced by using bioreactor and so inspite of high demand, rare sugars cannot be produced in the desired quantities.